Sistem Optimasi Bahan Baku Untuk Usaha Kue Bolu Menggunakan Metode Simpleks Berbasis Web - Moch. Rudy Kartono; Khaerul Ma’mur (CV. Multi Kreasi Media, 2022)
Optimization is the process of finding the best value from several alternative choices that can be applied to various fields such as production planning. In production planning at the 93 Cakes Shop, they still use the conventional method, namely determining the number of cakes by guessing, so that the impact on the profits obtained is not optimal. On the other hand, conventional production planning results in the use of raw materials being not optimal because when finished production there are residual raw materials that should be reused or lack of raw materials during the production process. Based on these problems, the simplex method is applied in order to provide solutions in production planning and can find out the benefits that will be obtained from the production process. The application of the simplex method is implemented on a web-based system. Based on system testing and manual calculations using the simplex method, the system output results that have been made are in accordance with what is expected. So that the system that has been created can provide solutions in production planning using available raw materials and provide information on the benefits that will be obtained from the results of production planning on the system.